Pengaruh Persepsi Konsumen Dan Keputusan Pembelian Terhadap Kepuasan Konsumen Pada PT Garuda Makmur Sentosa Pematangsiantar - Darwin Lie; Sisca Sisca; Sherly Sherly; Loist Abdi Putra; Andro Alex Chandra (Strategic: Journal of Management Sciences, 2021)
Objective. The purpose of this research is: To know the description of consumer perceptions, purchasing decisions, and consumer satisfaction at PT Garuda Makmur Sentosa Pematangsiantar. To determine the effect of consumer perceptions and purchasing decisions on consumer satisfaction at PT Garuda Makmur Sentosa Pematangsiantar. Research Methods. The research design used in writing this research is library research and field research. Data collection techniques used in this research are questionnaire method, interview method and documentation method. Results. Consumers agree with their perceptions, purchase decisions are good, and customer satisfaction is satisfied. The results of the regression analysis are = 8.302 + 0.448 X1 + 0.400 X2, meaning that consumer perceptions and purchasing decisions have a positive and significant effect on consumer satisfaction. The results of the correlation analysis obtained a value of r = 0.789, meaning that there is a strong and positive relationship between consumer perceptions and purchasing decisions with consumer satisfaction. The value of the coefficient of determination R = 0.623 means that the level of consumer satisfaction can be explained by consumer perceptions and purchasing decisions of 62.3%. The research hypothesis H0 is rejected, meaning that consumer perceptions and purchasing decisions have a positive and significant effect on consumer satisfaction at PT Garuda Makmur Sentosa Pematangsiantar either simultaneously or partially. Conclusion. The results of the qualitative descriptive analysis on perceptions both in terms of selective attention, selective distortion and selective retention got an average value of 3.85. Then the highest average value of 4.20 for the dimension of selective attention with an indicator of paying attention to banners. While the lowest average value is 3.27 on the selective retention dimension with indicators of previous experience and beliefs about product quality. The results of qualitative descriptive analysis on purchasing decisions both in terms of identifying the problem of needs, seeking information, evaluating alternatives, purchasing decisions, and post-purchase behavior got an average value of 3.96. Then the highest average value of 4.23 on the dimensions of purchasing decisions with indicators of consumer confidence. While the lowest average value of 3.17 on the dimensions of purchasing decisions with indicators of consumer decisions. The results of qualitative descriptive analysis on consumer satisfaction in terms of product and service quality, price structure, convenience of procedures, and consumer support got an average score of 3.96. The highest average value is 4.30 on the dimensions of product and service quality with product completeness indicators and also on the convenience dimension of procedures with service procedures indicators with the highest average value of 4.30. While the lowest average value is 3.27 on the dimension of consumer support with indicators of the speed of service provided and handling of complaints submitted.